Dual Task Effects on Speed and Accuracy During Cognitive and Upper Limb Motor Tasks in Adults With Stroke Hemiparesis - Kim, Hogene; Kim, Hyun-Ki; Kim, Nayoung; Nam, Chang S. (Frontiers in Human Neuroscience, 2021)
Background Adults with stroke need to perform cognitive–motor dual tasks during their day-to-day activities. However, they face several challenges owing to their impaired motor and cognitive functions. Objective This case-controlled pilot study investigates the speed and accuracy tradeoffs in adults with stroke while performing cognitive–upper limb motor dual tasks. Methods Ten adults with stroke and seven similar-aged controls participated in this study. The participants used a robotic arm for the single motor task and participated in either the serial sevens (S7) or the controlled oral word association test (COWAT) for single-cognitive task. For the dual task, the participants performed the motor and cognitive components simultaneously. Their speed and accuracy were measured for the motor and cognitive tasks, respectively. Results Two-sample t-statistics indicated that the participants with stroke exhibited a lower motor accuracy in the cross task than in the circle task. The cognitive speed and motor accuracy registered by the subjects with stroke in the dual task significantly decreased. There was a negative linear correlation between motor speed and accuracy in the subjects with stroke when the COWAT task was performed in conjunction with the cross task (ρ = −0.6922, p = 0.0388). Conclusions This study proves the existence of cognitive–upper limb motor interference in adults with stroke while performing dual tasks, based on the observation that their performance during one or both dual tasks deteriorated compared to that during the single task. Both speed and accuracy were complementary parameters that may indicate clinical effectiveness in motor and cognitive outcomes in individuals with stroke.